2016
DOI: 10.1039/c5nr09128d
|View full text |Cite
|
Sign up to set email alerts
|

Silicon monoxide – a convenient precursor for large scale synthesis of near infrared emitting monodisperse silicon nanocrystals

Abstract: While silicon nanocrystals (ncSi) embedded in silicon dioxide thin films have been intensively studied in physics, the potential of batch synthesis of silicon nanocrystals from the solid-state disproportionation of SiO powder has not drawn much attention in chemistry. Herein we describe some remarkable effects observed in the diffraction, microscopy and spectroscopy of SiO powder upon thermal processing in the temperature range 850-1100 °C. Quantum confinement effects and structural changes of the material rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 48 publications
(78 reference statements)
3
43
0
Order By: Relevance
“…This assumption is supported by accurate theoretical calculations which show the absence of a barrier for the SiO + SiO → (SiO) 2 and SiO + (SiO) 2 → (SiO) 3 reactions. Although a study by Pimental et al 26 reported a modest barrier for the latter (trimerisation) reaction, we could not verify this result and agree with the conclusion of Avramov et al 21 that a barrier for trimerisation does not exist.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…This assumption is supported by accurate theoretical calculations which show the absence of a barrier for the SiO + SiO → (SiO) 2 and SiO + (SiO) 2 → (SiO) 3 reactions. Although a study by Pimental et al 26 reported a modest barrier for the latter (trimerisation) reaction, we could not verify this result and agree with the conclusion of Avramov et al 21 that a barrier for trimerisation does not exist.…”
supporting
confidence: 60%
“…1 Control of segregation in SiO yields systems of sized controlled quantum+confined nanoparticles of silicon 2 or SiO x 3 embedded in a SiO 2 matrix, which are of great interest for light emission applications (e.g. biomedical imaging).…”
Section: " #mentioning
confidence: 99%
“…Thermal treatment of SiO in a 5% H 2 /Ar environment causes a redox disproportionation reaction in which the formally Si(II) in SiO is simultaneously reduced to Si(0) and oxidized to Si(IV). The so-formed Si(0) undergoes nucleation and growth to form ncSi in a SiO 2 matrix25. The size of the produced ncSi is within the range of 2–7 nm (ref.…”
Section: Resultsmentioning
confidence: 99%
“…The XRD pattern of synthesized SiO x -NPs is shown in Figure 3(b), red line, the Si (111, 220) diffraction peak. Further, Sun, W. et al, the commercial SiO precursor, has only two broad humps centered at ~23 and ~51 degrees and was observed in the XRD pattern [17]. In this context, the characteristics of synthesized SiO x -NPs which have a 0.91 x value are very close to the SiO.…”
Section: Introductionmentioning
confidence: 91%